2018
DOI: 10.1111/sms.13248
|View full text |Cite
|
Sign up to set email alerts
|

Validation of body composition using bioelectrical impedance analysis in children according to the degree of obesity

Abstract: This study aimed to validate body composition analysis using bioelectrical impedance analysis (BIA) against dual-energy X-ray absorptiometry (DXA) in children with obesity and to compare agreement between BIA and DXA according to their degree of obesity. Three hundred and sixteen children aged 6-17 years participated in the Intervention for Childhood and Adolescents Obesity via Activity and Nutrition study. We divided participants by body mass index (BMI) percentile (group 1: mild to moderate obesity; group 2:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 35 publications
2
28
0
2
Order By: Relevance
“…In our study, the biases of Slg‐Eq and BIA compared with DXA were lower as the adiposity levels increased, especially when Slg‐Eq was used. In line with our findings, the study of Seo et al found better agreement between BIA and DXA in the group of children and adolescents with severe obesity than the group with mild to moderate obesity. Opposite findings were found by Freedman et al in children and adolescents aged 5 to 18 years, ranked by the sum of SKF and classified in four sum categories according to the 33rd, 67th, and 90th percentiles within each sex.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, the biases of Slg‐Eq and BIA compared with DXA were lower as the adiposity levels increased, especially when Slg‐Eq was used. In line with our findings, the study of Seo et al found better agreement between BIA and DXA in the group of children and adolescents with severe obesity than the group with mild to moderate obesity. Opposite findings were found by Freedman et al in children and adolescents aged 5 to 18 years, ranked by the sum of SKF and classified in four sum categories according to the 33rd, 67th, and 90th percentiles within each sex.…”
Section: Discussionsupporting
confidence: 93%
“…In this regard, the available information has been scarce. Three studies have compared BIA with DXA in children and/or adolescents with obesity , and one study compared Slg‐Eq with DXA . 2) Although it has been widely used, BFP has not been suggested as a good measure for overall adiposity and to predict health‐related outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…Although no proportional bias was detected in the whole dataset, we observed marginally increased absolute bias within each subgroup, possibly due to fewer measurements and high leverage points of samples at low and high BMIZ (Table 4). Seo et al [44] performed validation of BIA versus DXA in children according to the degree of obesity and found better agreement between DXA and BIA for children with severe obesity than for children with mild to moderate obesity. Conversely, other studies suggested that bias is proportional to the level of body fat as either the adipose tissue or the high relative amount of extracellular water for overweight and TBW (kg) ¼ 0.44 RI (cm 2 /U) þ 0.12 weight (kg) þ 0.33 sex (male ¼ 1, female…”
Section: Discussionmentioning
confidence: 99%
“…However, one must note that results of studies comparing the BIA method with DXA indicate that BIA in slim subjects will tend to overestimate body fatty tissue, while in overweight subject, the fatty tissue contents will be underestimated as compared with densitometry [6,17,18]. Studies conducted by Sluytera, Wan, Seo, and ourselves indicate that the rate of underestimation of body fatty tissue content, determined using the BIA method, as compared with DXA, increased with the increased fatty tissue contents [18][19][20][21]. Such results were observed in both children and adults.…”
Section: Discussionmentioning
confidence: 99%